The European Union as a Global Actor Trade, Finance and Climate Policy - Lütz, Susanne; Leeg, Tobias; Otto, Daniel; Woyames Dreher, Vincent (Springer Texts in Political Science and International Relations, 2021)
XI, 218 p. 7 illus.